Estudo comparativo entre esfregaços de sangue total, periférico e esplênico para diagnóstico de piroplasmose em equinos da Paraíba - Queiroz, Erika de Lourdes Gomes de (2020)
Equine piroplasmosis, also known as babesiosis, is a disease caused by the protozoa Babesia caballi and Theileria equi that affects horses, donkeys, zebras and mules transmitted mainly by ticks. The objective of the study was to compare the results obtained with the use of whole blood smears, ear tip and splenic puncture samples and to verify a better simple and precise methodology for the diagnosis of piroplasmosis in subclinical horses in of Paraíba State in Northeastern, Brazil. In the period from June to November 2019, a total of 90 horses were evaluated, with an average weight of 350 kg, aged between 2 and 25 years, from both sexes. The frequency of animals positive for smear of whole blood collected from the venipuncture of the jugular (60% Babesia caballi; 17,8% Theileria equi), in splenic blood (55,6% Babesia caballi; 11,1% Theileria equi) and in blood collected from the internal auricular vein (48,9% Babesia caballi; 11,1% Theileria equi), respectively. The results obtained by this study revealed that 65 animals were positive in at least one of the techniques and 25 were negative in all techniques. There was no significant association between infection and ticks. The three methods are easy to perform, safe and little invasive, but the blood smear from the jugular was the most effective in detecting Piroplasmosis in horses.